1997
DOI: 10.1007/bf02238768
|View full text |Cite
|
Sign up to set email alerts
|

The rheumatoid wrist: Bilateral MR analysis of the distribution of rheumatoid lesions in axial plan in a female population

Abstract: In this case-control study, we analyzed 146 wrists: a) to search for the distribution pattern of the rheumatoid lesions and, b) to correlate the distribution pattern of these lesions with the clinical parameters. Thirty-one patients with rheumatoid arthritis (RA) and 42 controls-all women-were examined by means of a bilateral MR fast field echo (FFE) sequence, in axial plan. The wrist was divided into three regions: metacarpal (level I), carpal (level II) and radioulnar (level III). Erosions were present in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…Furthermore, in these studies, the MR images are most often obtained and evaluated in 1 plane only (6,8,(10)(11)(12)(13)(14), increasing the risk of misinterpretations, particularly due to partial volume artifacts being wrongly interpreted as erosive changes or synovitis. Bone marrow edema was assessed in only a few studies (6)(7)(8)11), and only 1 report describes dynamic contrast-enhanced MRI of MCP joints in the peripheral joints of healthy persons (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in these studies, the MR images are most often obtained and evaluated in 1 plane only (6,8,(10)(11)(12)(13)(14), increasing the risk of misinterpretations, particularly due to partial volume artifacts being wrongly interpreted as erosive changes or synovitis. Bone marrow edema was assessed in only a few studies (6)(7)(8)11), and only 1 report describes dynamic contrast-enhanced MRI of MCP joints in the peripheral joints of healthy persons (15).…”
mentioning
confidence: 99%
“…Furthermore, in these studies, the MR images are most often obtained and evaluated in 1 plane only (6,8,(10)(11)(12)(13)(14), increasing the risk of misinterpretations, particularly due to partial volume artifacts being wrongly interpreted as erosive changes or synovitis. Bone marrow edema was assessed in only a few studies (6)(7)(8)11), and only 1 report describes dynamic contrast-enhanced MRI of MCP joints in the peripheral joints of healthy persons (15). The objectives of the present study were 1) to explore the presence of bone changes resembling erosions, bone marrow edema, and soft tissue changes resembling synovitis in MCP and wrist joints of healthy persons on MR images obtained and evaluated according to the latest recommendations of the international initiative to harmonize outcome measures in rheumatology (Outcome Measures in Rheumatology Clinical Trials [OMERACT]) (16); and 2) to compare the MRI findings with conventional radiographic, clinical, and biochemical findings.…”
mentioning
confidence: 99%
“…A study of wrists in 31 women who had RA and 42 female controls showed that erosions were present in 97% of patients who had RA [58]. In this study, most lesions were found at the radial force-bearing column of the wrist and more erosions were present on the right side.…”
Section: Erosionsmentioning
confidence: 85%
“…In this study, most lesions were found at the radial force-bearing column of the wrist and more erosions were present on the right side. The study found that 14% of controls also showed erosions [58]. Other studies, however, showed no erosions in controls [59,60].…”
Section: Erosionsmentioning
confidence: 95%
“…Magnetic resonance imaging (MRI) is a valuable adjunct in assessing the anatomic characteristics of the carpal tunnel as well as the degree of synovial proliferation [ 35 ]. Pierre-Jerome et al [ 36 ] noted that 96 and 70 % of patients with RA undergoing a wrist MRI demonstrated synovial hypertrophy and a hyperintense signal in the median nerve.…”
Section: Carpal Tunnel Syndromementioning
confidence: 99%